A PDMS Film Structured Optical fiber Ultrasonic Sensor with high Sensitivity and Wide Response Range characteristics. Issue 2 (April 2021) - Li, Long; Liu, Shuaicheng; Hao, Zhiyuan; Song, Ming; Wang, Guanjun; Huang, Mengxing
Abstract: This paper proposes an implementation method of the optical fiber FP pressure ultrasonic sensor with a controllable cavity length and a variable membrane, in order to effectively improve the sensitivity and response range of the optical fiber Fabry-Perot (FP) ultrasonic sensor. The optical fiber FP ultrasonic sensor with PDMS film structure proposed in this paper has obvious advantages in improving sensitivity and response range.